IMPLEMENTASI PROGRAM PENCEGAHAN STUNTING DI PUSKESMAS KEDUNG I KABUPATEN JEPARA - Alvina Ayu Wardani; , Dewi Rostyaningsih; Aufarul Marom (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2023)
Stunting is a form of growth faltering due to the accumulation of long-lasting nutritional inadequacies. Kedung sub-district has the highest stunting rate in Jepara district. This study aims to analyze the implementation of the stunting prevention program and what factors hinder the implementation of the stunting prevention program at Puskesmas Kedung I, Jepara Regency. This research uses a qualitative approach with primary data collection techniques, observation, and interviews. Secondary data collection techniques, namely data published or used by organizations that are not processing them. The results of the research Implementation of stunting prevention has been carried out in accordance with output indicators with the criteria of access, coverage, service delivery, accountability, and program suitability to needs. The implementation of the stunting prevention program at Puskesmas Kedung I has been carried out quite well, there are inhibiting factors in the criteria of access, coverage, service delivery, and program suitability to needs. The obstacles in the implementation of the stunting prevention program are the lack of awareness of the target group of the importance of preventing stunting, difficulty in monitoring the target group, a limited budget although it can still be overcome by collaboration between villages with the same target, namely stunting prevention, and the division of time in implementing the prevention program.